Early initiation of antiretroviral treatment: Challenges in the Middle East and North Africa - Sardashti, Sara (World journal of virology, 2015)
New World Health Organization guidelines recommend the initiation of antiretroviral treatment (ART) for asymptomatic patients with CD4+ T-cell counts of ≤ 500 cells/mm(3). Substantial reduction of human immunodeficiency virus (HIV) transmission is addressed as a major public health outcome of this new approach. Middle East and North Africa (MENA), known as the area of controversies in terms of availability of comprehensive data, has shown concentrated epidemics among most of it's at risk population groups. Serious challenges impede the applicability of new guidelines in the MENA Region. Insufficient resources restrict ART coverage to less than 14%, while only one fourth of the countries had reportable data on patients' CD4 counts at the time of diagnosis. Clinical guidelines need to be significantly modified to reach practical utility, and surveillance systems have not yet been developed in many countries of MENA. Based on available evidence in several countries people who inject drugs and men who have sex with men are increasingly vulnerable to HIV and viral hepatitis, while their sexual partners - either female sex workers or women in monogamous relationships with high-risk men - are potential bridging populations that are not appropriately addressed by regional programs. Research to monitor the response to ART among the mentioned groups are seriously lacking, while drug resistant HIV strains and limited information on adherence patterns to treatment regimens require urgent recognition by health policymakers. Commitment to defined goals in the fight against HIV, development of innovative methods to improve registration and reporting systems, monitoring and evaluation of current programs followed by cost-effective modifications are proposed as effective steps to be acknowledged by National AIDS Programs of the countries of MENA Region.